RELATIONSHIP AMONG O, MG ISOTOPES AND THE PETROGRAPHY OF TWO SPINEL-BEARING COMPOUND CHONDRULES - Maruyama S.; Yurimoto H. (My University, 2003)
The petrological properties, and O and Al-Mg isotopic compositions of two spinel-bearing chondrules from the Allende CV chondrite were investigated using scanning electron microscopy and secondary ion mass spectrometry. A coarse spinel grain in a barred-olivine (BO) chondrule is less enriched in 16O (Δ17O ~ -5%%; Δ17O = δ17O - 0.52 δ18O), whereas smaller spinel grains in a plagioclase-rich chondrule member of a compound chondrule are extremely 16O-rich (Δ17O ~ -17%%) and the spinels have a strongly serrated character. The petrological features and 16O-enrichments of the spinels in the plagioclase-rich chondrule indicate that spinels originating in coarse-grained Ca-Al-rich Inclusions (CAIs) were incorporated into chondrule precursors and survived the chondrule-forming event. The degree of 16O-excesses among minerals within each chondrule is correlated to the crystallization sequences. This evidence suggests that the O isotopic variation among minerals may have resulted from incomplete exchange of O isotopes between 16O-rich chondrule melt and 16O-poor nebular gas. Aqueous alteration also has changed the O-isotope compositions in the mesostasis. The feldspathic mesostasis in the BO chondrule shows a disturbed Mg-Al isochron indicating that the BO chondrule experienced secondary alteration. While plagioclase in the plagioclase-rich chondrule member of the compound chondrule shows slight 26Mg-excesses corresponding to (26Al/27Al)0 = [4.6+/-4.0(2σ)] x 10-6, nepheline formed by secondary alteration shows no detectable excess. The Al-Mg isotopic system of these chondrules was disturbed by aqueous alteration and thermal metamorphism on the Allende parent body.